Aggressive extensive cardiac mass in an HIV-1-infected patient: should we go for comfort therapy?. Issue 3 (4th May 2017) - Vervloet, Delphine MTF; De Pauw, Michel; Demulier, Laurent; Vercammen, Jan; Terryn, Wim; Steel, Eva; Vandekerckhove, Linos
Abstract : Cardiac masses are rare, the differential diagnosis includes infections with vegetations or abscesses, neoplasms, thrombi, and structural abnormalities. A pathology specimen is essential in therapeutic strategy planning for a cardiac mass, also if the primary imaging findings look dramatic at the start. Even in an inoperable setting, a life-saving therapy might be available. We report a case of a 49-year-old man, known with HIV-1, who was several times admitted with pericarditis. Now he was hospitalized with progressive lower limb edema, atrial fibrillation and detection of a giant cardiac mass in left and right atrium with infiltration of surrounding tissues. Given the extent and invasiveness of the mass, he was inoperable. Biopsy specimen was obtained and staging was performed by PET-CT scan. The diagnosis of stage IV Burkitt lymphoma with predominant extranodal cardiac involvement was withheld wherefore promptly aggressive therapy was started according to the GMALL B-NHL86 protocol. The therapy was downgraded to R-CHOP due to tolerance problems. He achieved a complete remission and during follow-up no relapse was detected.